Particle Production in Ultrarelativistic Heavy-Ion Collisions: A Statistical-Thermal Model Review - S. K. Tiwari; C. P. Singh (Advances in High Energy Physics)
The current status of various thermal and statistical descriptions of particle production in the ultrarelativistic heavy-ion collisions experiments is presented in detail. We discuss the formulation of various types of thermal models of a hot and dense hadron gas (HG) and the methods incorporated in the implementing of the interactions between hadrons. It includes our new excluded-volume model which is thermodynamically consistent. The results of the above models together with the experimental results for various ratios of the produced hadrons are compared. We derive some new universal conditions emerging at the chemical freeze-out of HG fireball showing independence with respect to the energy as well as the structure of the nuclei used in the collision. Further, we calculate various transport properties of HG such as the ratio of shear viscosity-to-entropy using our thermal model and compare with the results of other models. We also show the rapidity as well as transverse mass spectra of various hadrons in the thermal HG model in order to outline the presence of flow in the fluid formed in the collision. The purpose of this review article is to organize and summarize the experimental data obtained in various experiments with heavy-ion collisions and then to examine and analyze them using thermal models so that a firm conclusion regarding the formation of quark-gluon plasma (QGP) can be obtained.